2014
DOI: 10.3354/meps10769
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a morbillivirus epizootic on long-finned pilot whales Globicephala melas in Spanish Mediterranean waters

Abstract: Long-finned pilot whales Globicephala melas are a commonly encountered species in the Mediterranean Sea. In 2006−2007, an outbreak of the dolphin morbillivirus in the Western Mediterranean resulted in increased mortality of this species. The aim of this study was to determine whether survival rates differed between clusters of Spanish Mediterranean pilot whales, and how the epizootic influenced these survival rates. Photo-identification surveys were conducted between 1992 and 2009. Association indices were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
2
11
1
Order By: Relevance
“…The observed decline is likely related to the epizootic, considering the large increase of morbillivirus‐positive strandings observed during the same period (Fernández et al, ). Moreover, the survival rate decrease was similar to what was estimated for some social clusters (27%) of the neighbouring Alboran Sea pilot whales (Wierucka et al, ), although there it did not affect the entire population. Singer, Zeigenfuss, and Spicer () suggested that a terrestrial mammal population larger than 250 individuals with a large home range and migratory movements (i.e.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The observed decline is likely related to the epizootic, considering the large increase of morbillivirus‐positive strandings observed during the same period (Fernández et al, ). Moreover, the survival rate decrease was similar to what was estimated for some social clusters (27%) of the neighbouring Alboran Sea pilot whales (Wierucka et al, ), although there it did not affect the entire population. Singer, Zeigenfuss, and Spicer () suggested that a terrestrial mammal population larger than 250 individuals with a large home range and migratory movements (i.e.…”
Section: Discussionsupporting
confidence: 86%
“…Worldwide, CeMV epizootics have caused higher stranding rates over a few months locally but could last for years when the virus was transmitted over larger areas (Van Bressem et al, ). However, results found in this study and in the nearby Alboran Sea (Wierucka et al, ) show that the effects, whether direct or indirect, can span over at least 5 years. Cumulative effects of some of the following hypotheses could potentially explain these results: A post‐epizootic chronic effect of the morbillivirus as reported for infected individual striped dolphins in the Spanish Mediterranean coast 4 years after the epizootics (Domingo et al, ; Soto et al, ). High immunosuppressive contaminant levels, such as polychlorinated biphenyls and dichlorodiphenyltrichloroethanes and high biomarker responses (CYP1A1 and CYP2B) (Lauriano, Di Guardo, Marsili, Maltese, & Fossi, ).…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations